Angiogenesis-osteogenesis coupling and anti-osteoclastogenesis zoledronate intermixed calcium silicate metal-organic/inorganic hybrid coating on biodegradable zinc-based intramedullary nails for osteoporotic fracture healing - Junyu Qian; Haotian Qin; En Su; Jiaming Hou; Hui Zeng; Tianbing Wang; Deli Wang; Guojiang Wan; Yingqi Chen (Bioactive Materials)
Osteoporotic (OP) fractures remain a tough clinical challenge owing to their impaired healing outcome, which requires novel biomaterials with osteogenicity for effective healing. Metallic zinc (Zn) is attracting increasing attention for biodegradable intramedullary nails (IMNs) for OP fracture healing thanks to their comprehensive mechanical properties, biosafety, and bioactivity. However, the multiple biofunctions required for OP fracture healing have not been fully met by Zn. Herein, a zoledronate (ZA)-mediated calcium-zinc silicate (Ca(Zn)Si) metal-organic/inorganic hybrid coating was fabricated on Zn-based IMN by coordination chemistry driven via interactions between ZA and Ca2+/Zn2+ as well as in-situ directional growth of Ca(Zn)Si phase. The ZA&Ca(Zn)Si hybrid coating exhibited a homogeneous micro/nanostructure with a granular morphology, which prevented premature fracture failure of IMN in rat femur by ameliorating corrosion mode and decreasing degradation rate of the Zn matrix. More importantly, this hybrid coating enabled sustained release of Zn2+/Ca2+/Si4+ and ZA in the long term, achieving a remarkable effect on vascularized bone regeneration. The coated IMN enhanced angiogenesis–osteogenesis coupling through autocrine and paracrine effects between endothelial cells and bone marrow mesenchymal stem cells. Osteoclastogenesis was repressed by Zn2+ and ZA. This approach offers a new strategy for surface-engineering of biodegradable metals for bone fracture healing.